Simulation of resistance of modified wood washout protective agent - Цапко, Юрий Владимирович (Eastern-European Journal of Enterprise Technologies, 2014)
Using the developed computational and analytical method, the intensity of modifiers mass transfer from the treated wood was determined, and the effect of the wood preservative covering and water repellent on the flame retardant removal slowdown process was defined. The developed mathematical model and its numerical implementation method allow to determine the parameters of modifiers washout in wood and its covering into the environment, depending on the samples geometry, physical–chemical properties of substances, impregnating wood and their initial distribution in the covering material, wood and environment. In particular, it was established that, after the 100–th time step, reduction of the flame retardant concentration in the wood, covered with preservative was approximately 30 %, while using water repellent – only 4 %. The calculated thickness of the polymeric preservative covering for the mixture DSA–2, which causes destruction is 12,6∙10–6 m, while using water repellent – 29,5∙10–6 m. This allows to consider that using the water repellents considerably prevents the flame retardants escape from the modified wood and make a rational choice of agents to increase the service life of the treated wood.